Search for the rare decays W+ → D+sγ and Z → D0γ at LHCb - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (Chinese physics. C, High energy physics and nuclear physics, 2023)
A search for the rare decays and is performed using proton-proton collision data collected by the LHCb experiment at a centre-of-mass energy of 13, corresponding to an integrated luminosity of 2.0. No significant signal is observed for either decay mode and upper limits on their branching fractions are set using and decays as normalization channels. The upper limits are and at 95% confidence level for the and decay modes, respectively. This is the first reported search for the decay, while the upper limit on the branching fraction improves upon the previous best limit.
Online veröffentlicht: 7. August 2023
*LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, D. Gerick, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, C. Witola, A. Zhelezov (und 1051 weitere Personen)
Im Titel sind die Pluszeichen und die Zahl 0 hochgestellt sowie der Buchstabe "s" tiefgestellt
Gesehen am 22.05.2024